FTO promotes tumour proliferation in bladder cancer via the FTO/miR-576/CDK6 axis in an m6A-dependent manner - Guanwen Zhou (Nature Publishing Group, 2021)
Abstract The aberrant expression of fat mass and obesity-associated protein (FTO) has been confirmed to be associated with a variety of cancers and participates in the regulation of multiple biological behaviours. FTO plays an oncogenic role in bladder cancer, but few studies have focused on how FTO promotes bladder cancer progression by regulating miRNA synthesis. Here, we confirmed that FTO expression was significantly increased in bladder cancer and was associated with a poor prognosis. FTO overexpression promoted bladder cancer cell proliferation, whereas FTO knockdown inhibited bladder cancer cell proliferation. We also demonstrated that FTO promoted bladder cancer cell proliferation via the FTO/miR-576/CDK6 pathways. Taken together, our work revealed that FTO plays a critical role in bladder cancer and could be a potential diagnostic or prognostic biomarker for this disease.